The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.52229/pbmj.v4i1.56
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of depression and anxiety among heart failure patients in a tertiary care hospital of Faisalabad, Pakistan

Abstract: : Heart failure (HF) is a chronic illness with high prevalence and mortality, leading to economic burden of health due to prolonged hospital stay and re-admissions. Failure to comprehend the importance of identifying mental illnesses could lead to explanations that why the morbidity and mortality of heart failure patients endure to be very high. Objective: To determine the frequency of anxiety and depression in heart failure patients. Methods: It is a descriptive cross sectional study including 323 CHF patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A study done in Ethiopia revealed that the prevalence of depression and anxiety symptoms among hypertension patients was 27.2 and 32.7 %, respectively [ 10 ]. Other studies undertaken in Pakistan displayed that the prevalence of depression and anxiety among Heart failure patients was 55 % and 57 %, respectively [ 11 ]. In a study undertaken in Spain and Saudi Arabia showed that the prevalence of depression among heart failure patients was 48.5 % and 52.4 %, respectively [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study done in Ethiopia revealed that the prevalence of depression and anxiety symptoms among hypertension patients was 27.2 and 32.7 %, respectively [ 10 ]. Other studies undertaken in Pakistan displayed that the prevalence of depression and anxiety among Heart failure patients was 55 % and 57 %, respectively [ 11 ]. In a study undertaken in Spain and Saudi Arabia showed that the prevalence of depression among heart failure patients was 48.5 % and 52.4 %, respectively [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence is higher in low-and middle-income countries (LMICs) such as Pakistan (Fisher et al, 2012), where estimates for maternal anxiety range from 35% to 49% (Niaz et al, 2004;Waqas et al, 2015) and where challenges in the treatment of anxiety are exacerbated by the scarcity of mental health services (WHO World Mental Health Survey Consortium, 2004;Patel et al, 2010;Saxena et al, 2007). Risk factors for anxiety in Pakistan include social and relationship stressors such as lack of social support, gender inequalities, and intimate partner violence during pregnancy (Waqas et al, 2015).…”
Section: Introductionmentioning
confidence: 99%